Hubungan Tingkat Pengetahuan, Sikap Dan Motivasi Terhadap Kepatuhan Minum Obat Dengan Frekuensi Kekambuhan Pada Pasien Skizofrenia - fitri, nurwijaya; Savira, Cindy (Institut Citra Internasional, 2022)
Schizoprenia is a chronic, complex and heterogeneous disease that affect most of the functions of the psychological aspect, the impact is heavy As a resukt, individuals with schizophrenia can destroy aspects of the family, social roles, and dependence on antipsychotic drugs as a major factor in preventing recurrence and the emergence of symptom-symptom present in the patient. The purpose this study was determine the relationship between knowledge, attitudes and motivation towards medication adherence with frequency schizophrenia in the outpatient clinic in the Clinic of the Bangka Belitung Regional Mental Hospital in 2021. This study used a cross-sectional design. The number of responden is 59 people with sampling technique using quota sampling. Use statistical analysis of uil chi square on the mean 95% confidence level (? = 0,005) the results of this study found that there was a between knowledge (0,017), attitude (0,003) and motivation (0,016) with adherence to taking medication at the Outpatient Clinic Of mental Hospital in 2021.